Pengaruh Pengaruh Motivasi dan Beban Kerja Terhadap Turnover intention pada PT. Industri Jamu Borobudur Cabang Bali. - Krisna Putra, Ketut Alit Adi Sena; Kartika, I Made (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2023)
Paying attention to keeping turnover intention low is an important investment for the sustainability and long-term success of the company. For companies capable of providing high job motivation, as well as well-measured workloads and responsibilities, are crucial aspects to be considered. The main issue for the company is the high turnover rate. One of the causes of high turnover intention among employees is motivation and workload at PT. Industri Jamu Borobudur Bali branch. This study aims to analyze the influence of motivation and workload on turnover intention. The sample size used in this research is 53 respondents. Data analysis was conducted using instrument testing, classical assumption testing, multiple linear regression analysis, determination analysis, significance test (t-test), and significance test (F-test). The research results show a positive and significant partial as well as simultaneous influence between motivation and workload on turnover intention at PT. Industri Jamu Borobudur Bali branch